Financial Performance in Predicting Stock Return: Study on Non-Financial Companies Listed on IDX - Rizka, Nor Rahma (E-Jurnal Akuntansi; Vol 32 No 9 (2022), 2022)
Accounting and financial information are usually given to investors to help predicting the stock returns because the data has the value and historical. This study aims to examine how the ability of financial performance that represent leverage consisting of debt to asset ratio (DAR), debt to equity ratio (DER), and profitability including return on asset (ROA), return on equity (ROE), and net profit margin (NPM) in predicting stock returns. The research applies a final sample of 163 companies of non-financial sector registered in IDX in 2015-2019. This research applies analysis of multiple linear regression. The study results prove that DAR, ROE, NPM have no significant influence toward the stock returns. DER and ROA give such a significant and also negative influence on stock returns. These results mean that investors can consider DER and ROA in predicting stock returns as signals from accounting and financial data. Keyword: Debt to Asset Ratio, Debt to Equity Ratio; Return on Asset; Return on Equity; Net Profit Margin; Stock Return